USE OF FOREST STRATA BY THE SUMATRAN ORANG-UTANS: A CONSIDERATION OF FUNCTIONAL ASPECTS - JITO SUGARDJITO (Treubia, 1988)
Differences in travel height between age-sex classes of the Sumatran orangutans are determined by locomotory efficiency in relation to body weight. The distribution of travel height in relation to resting heights suggests also possible influence of predation. Travel height does hardly restrain diet choice, because differences in diet between sexes are not associated with differences in strata utilization with regard to feeding.